1994
DOI: 10.1083/jcb.126.5.1211
|View full text |Cite
|
Sign up to set email alerts
|

Beta-actin mRNA localization is regulated by signal transduction mechanisms.

Abstract: A b s t r a c t . B-actin mRNA is localized in the leading lamellae of chicken embryo fibroblasts (CEFs) (Lawrence, J., and R. Singer. 1986. Cell. 45:407-415), close to where actin polymerization in the lamellipodia drives cellular motility. During serum starvation B-actin mRNA becomes diffuse and nonlocalized. Addition of FCS induces a rapid (within 2-5 min) redistribution of B-actin mRNA into the leading lamellae. A similar redistribution was seen with PDGF, a fibroblast chemotactic factor. PDGFinduced B-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 65 publications
6
86
0
1
Order By: Relevance
“…The authors further showed that serum-induced 13-actin mRNA distribution is mediated through the GTPase signalling pathway. A similar conclusion was drawn by Singer's group in observing that PDGF-induced 1-actin mRNA was dependent on tyrosine kinase activity for redistribution in chicken embryo fibroblast and that the relocation of steady-state ,B-actin mRNA in serumcontaining media was inhibited by modulators of protein kinase A and C (Latham et al, 1994). These lines of evidence suggest that the signal transduction events modulate the dynamics of f-actin mRNA localization.…”
Section: Discussionsupporting
confidence: 65%
“…The authors further showed that serum-induced 13-actin mRNA distribution is mediated through the GTPase signalling pathway. A similar conclusion was drawn by Singer's group in observing that PDGF-induced 1-actin mRNA was dependent on tyrosine kinase activity for redistribution in chicken embryo fibroblast and that the relocation of steady-state ,B-actin mRNA in serumcontaining media was inhibited by modulators of protein kinase A and C (Latham et al, 1994). These lines of evidence suggest that the signal transduction events modulate the dynamics of f-actin mRNA localization.…”
Section: Discussionsupporting
confidence: 65%
“…While this does not demonstrate a direct interaction, it is consistent with the in situ hybridization data. Our data are particularly interesting in the context of the demonstration that myosin-IIB has been shown in fibroblasts to be required for the proper localization of β-actin mRNA in response to growth factors [Latham et al, 1994;Kislauskis et al, 1997;Latham et al, 2001]. From our pulse/chase experiments, myosin-Va appears to be responsible for mRNA transport from the nucleus to the periphery, where myosin-IIB could capture mRNAs.…”
Section: Discussionmentioning
confidence: 79%
“…It is interesting to note that EF1␣ localizes with actin filaments in protrusions but not with stress fibers. In chicken fibroblasts, serum stimulation leads to rapid localization of ␤-actin mRNA at the cell front similar to EFI␣ (Latham et al, 1994). Electron microscopy studies have shown that EF1␣ molecules colocalize with mRNA on actin filaments (Bassell et al, 1994).…”
Section: The Role Of Ef1␣ In Anchoring Versus Transport Of Mrnamentioning
confidence: 99%
“…Furthermore, this inhibitory effect caused by expression of GFP-domain III is significant because localization of the ␤-actin mRNA in these cells was suppressed to almost background level represented by the localizations of ␣-tubulin mRNA in normally cultured CEFs and ␤-actin mRNA in CEFs in serum-depleted culture ( Figure 11A, lanes 5 and 6). Localization of ␤-actin mRNA has been known to depend on the presence of serum in cell culture (Latham et al 1994), whereas ␣-tubulin mRNA was shown not to localize in cells (Shestakova et al, 1999). …”
Section: Domain III Of Ef1␣ Inhibits the Binding Of ␤-Actin Mrna To Ementioning
confidence: 99%